In Praise of Incremental Innovation in Higher Education - Moreno, Carlos (International Higher Education, 2024)
Disruption seems to be the new name of the game in higher education. As everything has to be “disruptive” in order to be valuable, we risk losing sight of the importance of traditional incremental innovation, especially in macro-universities. There is no doubt that higher education institutions around the globe have to continually change and adapt but is it really possible, or even desirable, for all institutions to adopt a disruptive approach?